The Influence of Job Satisfaction, Organisational Commitment, Work-Life Balance and Pay and Reward towards Employees’ Turnover Intention in Food and Beverage Industry Malaysia - Pei, Yook; Madhavedi, Sudhakar; Hoo, Wong Chee; Suhud , Usep (Journal of Posthumanism, 2025)
Purpose: This study examines how job satisfaction, organizational commitment, work-life balance, and pay and rewards influence employees’ turnover intentions in Malaysia’s Food and Beverage industry. Methodology: Using a quantitative approach, the study distributed questionnaires to F&B organizations, gathering responses from 400 participants. The data were analyzed using Multiple Linear Regression Analysis, Correlation analysis and Factor Analysis. Multiple linear regression assessed how turnover intention—the dependent variable—was influenced by independent variables. Findings: The study results highlight the importance of nurturing job satisfaction, strengthening organizational commitment, promoting work-life balance, and offering competitive pay and rewards to reduce employee turnover. Organizations that cultivate a positive work environment, provide career development and training opportunities, and actively engage employees are better positioned to retain talent, reduce costs, and build a stable, high-performing workforce. Novelty: This study explores employee turnover in Malaysia’s F&B service industry, a largely under-researched area, by examining the impact of job satisfaction, organizational commitment, work-life balance, and compensation. It enhances theoretical models and provides actionable insights to help businesses develop targeted retention strategies, improve workforce stability, and address industry-specific cultural and economic factors.